Childhood dental caries in context: associations with parental oral health literacy, parenting practices, stress, and socioeconomic status - Maria Eugênia Domingueti Rabelo Ribeiro; Lara Evangelista Orlandi; François Isnaldo Dias Caldeira; Leandro Araújo Fernandes; Lucas Guimarães Abreu; Murilo César do Nascimento; Daniela Coelho de Lima; Heloisa de Sousa Gomes (Frontiers in Dental Medicine, 2026)
Introduction Dental caries remains a global public health issue influenced by multiple family, psychosocial, and socioeconomic factors, including parental oral health literacy and parenting practices. However, the associations between parental oral health literacy, parental stress, parenting practices, and children's dental caries experience are still not fully understood. Therefore, this cross-sectional study evaluated the associations of parental oral health literacy, parental stress, parenting practices, and socioeconomic status with children's dental caries experience assessed during dental care. Methods A cross-sectional study involved children aged 4 to 12 attending the Pediatric Dentistry Clinic at the School of Dentistry, Federal University of Alfenas. Children underwent dental prophylaxis and a clinical examination to assess caries using the dmft/DMFT index. Parents’ oral health literacy was measured with the Brazilian version of the Rapid Estimate of Adult Literacy in Dentistry (BREALD-30), parental stress with the Parental Stress Scale (PSS), and family bonding with the Parenting Practices Inventory (PPI). Statistical analysis was performed using the Kruskal-Walli's test and Poisson regression, with a significance level of 5%. Results Among 134 parent–child dyads, children were mostly male (52.2%; n = 70; mean age: 7.64 ± 2.21 years), and parents/guardians were predominantly female (88.1%; n = 118; age: 29–40 years). Higher parental oral health literacy, more positive parenting practices, older parental age, and older child age were associated with lower dmft/DMFT values, whereas lower family income was associated with higher dmft/DMFT values. Conclusion Higher parental oral health literacy was associated with lower DMFT/dmft values in children. Parenting practices, socioeconomic status, parental age, and child age were also associated with children's dental caries experience.